Political will and personal belief : the decline and fall of Soviet communism - Hollander, Paul, 1932-2019 (Yale University Press, 1999)
"Paul Hollander focuses on the human aspects of the failure of Soviet communism. He examines how members of the Soviet political elite, leaders in communist Czechoslovakia and Hungary, high-ranking officials in agencies of control and coercion, and distinguished defectors and exiles experienced the erosion of ideals that undermined the political system they had once believed in."--Jacket